Technological and operating features of the AR-1000 reactors Generation III+ and small modular reactors MR-160 - Vashchenko, Volodymyr; Korduba, Irina; Zhukova, Olena (Kyiv National University of Construction and Architecture, 2021)
Technological and environmental analysis of the main characteristics of technological, operational and environmental safety in the context of progress in the main areas of development of reactor units such as VVER, MR-160 and AR-1000 for power units currently under development, design and construction is one of the most pressing issues development of world nuclear energy. This urgency in particular is due to the fact that on the basis of these technologies further development of Ukraine's nuclear energy is planned. The tasks of ensuring operational and radioecological safety for new generation power reactors are reduced to obtaining the lowest possible probability of events related to a possible accident, as well as the lowest possible probability of radiation consequences in compliance with all requirements of national and international regulations and recommendations adopted by a particular state and its civil society.